Editorial: Introduction to the special issue on conducting research syntheses on individual differences in SLA - Csizér, Kata; Albert, Ágnes; Piniel, Katalin (Studies in Second Language Learning and Teaching, 2022)
As systematic research syntheses and meta-analytic studies are becoming more prominent in the social sciences, especially in the fields of psychology and ed-ucation, it appears that applied linguists have also started to follow suit (In’nami et al., 2019). One of the main reasons for this is that abundant knowledge has accumulated through the years about second and foreign lan-guage (L2) learning and teaching, making the time ripe to systematically syn-thesize the research findings in order to draw further conclusions and identify paths future studies could take. This is also true for the subfield of individual differences (IDs) research within applied linguistics, where proliferation in the number of studies focusing on individual learner differences with respect to a large variety of issues has been witnessed in the past decades. Hence, we saw it timely to compile a special issue on research synthesis in the subfield of IDs in L2 learning. We formulated the following aims to guide our venture: First of all, we intend to inform scholars of the nature and utility of research syntheses in our field. Second, we hope that the articles included in the special issue would serve as examples for researchers wishing to embark on conducting similar studies. Our third and not negligible aim was to see what tendencies regarding particular individual differences can be outlined based on previous research results. In order for the readers to make the most of these articles, in this editorial introduction we would like to articulate how we see the role of research synthesis in general and meta-analysis in particular in our field. To this end, we will offer relevant definitions and a short discussion on their utility. We will then move on to outline very generic guidelines for conducting sys-tematic research syntheses, and, finally, we will summarize the studies includ-ed in the volume and their contribution to the field of research on IDs.